Tocilizumab in the Treatment of Chronic Antibody-Mediated Rejection Post Kidney Transplantation: Clinical and Histological Monitoring - Noble, Johan; Giovannini, Diane; Laamech, Reda; Imerzoukene, Farida; Janbon, Bénédicte; Marchesi, Laura; Malvezzi, Paolo; Jouve, Thomas; Rostaing, Lionel (Frontiers in Medicine, 2021)
Introduction: Chronic antibody-mediated rejection (cAMR) has very few effective therapeutic options. Interleukin-6 is an attractive target because it is involved in inflammation and humoral immunity. Therefore, the use of tocilizumab (anti-IL6 receptor, TCZ) is a potential valuable therapeutic option to treat cABMR in kidney-transplant (KT) recipients. Material and methods: This single-center retrospective study included all KT recipients that received monthly TCZ infusions in the setting of cABMR, between August 2018 and July 2021. We assessed 12-month renal function and KT histology during follow-up. Results: Forty patients were included. At 12-months, eGFR was not significantly different, 41.6 +/-17 vs. 43 +/- 17 mL/min/1.73m2 (p=0.102) in patients with functional graft. Six patients (15%) lost their graft: their condition was clinically more severe at the time of first TCZ infusion. Histological follow-up showed no statistical difference in the scores of glomerulitis, peritubular capillaritis, and interstitial fibrosis/tubular atrophy (IFTA). Chronic glomerulopathy score however, increased significantly over time; conversely arteritis and inflammation in IFTA ares improved in follow-up biopsies. Conclusion: In our study, the addition of TCZ prevented clinical and histological worsening of cABMR in KT recipients, except for more severely ill patients. Randomized studies are needed to clarify the risk/benefit of TCZ in cABMR.